Eksistensi dan Implementasi Madrasah Sebagai Lembaga berbasis Masyarakat - Moh. Solehuddin (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2019)
Islamic educational institutions have a dual role in addition to preparing students to master knowledge that is useful for their future life, they also have a responsibility as a forum for forming children's religious character in navigating social life and the hereafter. Madrasas, like Islamic educational institutions, also play a role in instilling and developing community values. The existence of a shift in values ??and demands for modernization has caused educational institutions to be dragged into pragmatism which emphasizes the orientation of students' graduation only. This pragmatic demand seems to negate the main goal of preparing students to become complete human beings: knowledgeable, have faith, have social sensitivity and character.